PENGARUH PENGGUNAAN MEDIA SARUNG TANGAN HURUF TERHADAP KEMAMPUAN MENGENAL HURUF PADA ANAK USIA 4-5 TAHUN DI PAUD AS-SHIFA CITRA KECAMATAN TAMPAN KOTA PEKANBARU - Alpina, Resti; Novianti, Ria; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research purposed is to know the effect of the use of letter gloves on the ability to recognize letters of children aged 4-5 years in PAUD As-Shifa Citra Kecamatan Tampan Kota Pekanbaru. The sample used in this study were 15 students. Method that use is experiment One Group Pretest –Posttest Design. The data collection techniques used are observation and documentation. Data analysis technique used t-test with SPSS 17.0. According to result of experimental hypothesi there is effect of media use of letter gloves on the ability to recognize letters in children aged 4 - 5 years in PAUD As-Shifa Citra Kota Pekanbaru. This can be known from the analysis of data obtained thitung = 10,954 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is a difference in the ability to recognize letters of significant after the use of media use of letter gloves on the ability to recognize letters in children aged 4 to 5 years in PAUD As-Shifa Citra Kota Pekanbaru. The effect of media use of letter gloves on the ability to recognize letters of children aged 4 to 5 years in PAUD As-Shifa Citra Kecamatan Tampan Kota Pekanbaru regency of 56,60%.Keywords: Ability to recognize letters, Media of letter gloves